The key features of highly effective training units in obstetrics and gynaecology. (13th April 2020) - O'Sullivan, Marie; Newell, Sarah; Frost, Jonathan; Mountfield, Joanna
Abstract : Key content: High‐quality training environments may increase job satisfaction, reduce attrition and promote excellence in education and training. Data on training are collected through the General Medical Council Survey, Training Evaluation Form and Workforce Survey. Attrition rates in obstetrics and gynaecology are high (30%) – among the highest across all specialties – and reasons for this include morale and undermining, training processes and paperwork, support and supervision, work–life balance, National Health Service environment and job satisfaction. High attrition rates affect the remaining workforce and can have a negative impact on the working environment. Learning from excellence may be more helpful than focusing on negative aspects of poor training. Learning objectives: To understand the fundamental features of highly performing units. To identify contributors to poor training performance. To implement a simple structure for analysing training performance. To learn simple interventions that can improve training.